PERENCANAAN TEKNIS DRAINASE JALAN SAUDARA KOTA MEDAN - Dhani Wardhana; Siti Zulfa Yuzni; Mhd Dominique Mendoza (Universitas Negeri Medan, 2023)
ABSTRACTJalan Saudara which is located in Medan Kota Subdistrict the city of Medan with the boundary between the Jalan SM Raja intersection and the Jalan Bahagia intersection with a length of 743 m is very prone to flooding, especially during the rainy season. The dimensions of the drainage channels are small and vary between open and closed channels. Drainage problems on your road a) The area of the inundation area is 1000 meters, b) The width of the inundation area is 6 m, c) The inundation height is 20 cm, d) Inundation duration is 15 minutes, e) Inundation frequency is every heavy rain and f) The causes of flooding are due to the dimensions of the canal small and there is a blockage of several damaged culverts. The aim of the research is to design the dimensions of the drainage channels along Jalan Saudara so that they can accommodate all water waste activities and are expected to overcome flooding in the area. The methodology is carried out by analyzing hydraulics and hydrological analysis to determine the calculation of maximum rainfall, rainfall intensity, time of concentration and discharge of runoff, flow velocity in drainage channels, design of channel discharge, and design of channels. The calculation results obtained a) The intensity of maximum rainfall with the analysis of various methods, it was found that the Log Pearson III method was the best used. This was done by statistical tests with chi-square and with Smirnov-Kolmogorov, b) The detailed design of the drainage using precast concrete in the form of a closed U-Ditch with dimensions of 120 cm x 100 cm with a height varying between 120 cm and 160 cm. c) At a certain point, drainage using Box culverts with dimensions of 150 cm x 100 cm with a height of 150 cm.Kewords: Saudara Street, Drainage, Technical Planning